1,2-Benzenedithiol and Toluene-3,4-dithiol Arsenic(III) Complexes—Synthesis, Structure, Spectroscopic Characterization and Toxicological Studies - Lyczko, Monika (Molecules, 2019)
A new group of arsenic(III) complexes with bidentate S,S-donor ligands, 1,2-benzenedithiol (Ph(SH)(2)) and toluene-3,4-dithiol (MePh(SH)(2)), were synthesized. The use of arsenic(III) iodide and bromide promoted the formation of neutral complexes (1–4) with the general formula AsX(LS(2)) (X = I or Br, L = MePh or Ph). The crystal structures of these compounds were determined using single-crystal X-ray diffraction (scXRD). Unlike other arsenic(III) complexes, AsBr(PhS(2)) complex (2) was found to crystallize with a rare 13 molecules in the asymmetric unit. The compounds were also characterized by conventional physico-chemical techniques (Fourier transform infrared (FT-IR) spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, nuclear magnetic resonance (NMR), high-performance liquid chromatography (HPLC), elemental analysis (EA) and electrospray ionization-mass spectrometry (ESI-MS)). The results from structural and spectroscopic studies were supported by DFT calculations using the B3LYP/LANL2DZ and (or) 6-31+G(d,p) approaches. The cytotoxicity of these complexes was estimated for human acute promyelocytic leukemia cell line (NB4). They exhibited remarkable cytotoxicities after 48 h of treatment with IC(50) equal to about 10 µM and 40 µM for complexes with 1,2-benzenedithiolato and toluene-3,4-dithiolato ligand, respectively. Their toxicity was lower than that of commonly used chemotherapeutic As(2)O(3) (IC(50) = 1.4 µM).